Towards a cyclical concept of real-world laboratories. A transdisciplinary research practice for sustainability transitions. - (:unkn) unknown (Routledge, 2018)
Der Artikel verfolgt zwei Ziele: Erstens sollen Schlüsselkomponenten des Reallabors benannt werden. Zweitens soll gezeigt werden, wie diese Schlüsselkomponenten in die Foschungspraxis integriert werden können. Als Beispiel dient das Projekt "Wohlstands-Transformation Wuppertal - ein urbanes Transformationslabor für nachhaltiges Wirtschaften" (WTW).

The transformative research approach of Real-World Laboratories (RWL) has recently attracted attention in German sustainability science. Some definitions and understandings have been published, but guidelines and procedural quality criteria for establishing and running a RWL are still missing. To address this gap, this article has two aims. First, it aims to derive key components of RWLs from the current discourse on RWLs and similar, but more elaborated research approaches. Second, it aims to transfer these key components into a comprehensive research practice. This practice is illustrated by the RWL process in the project "Well-being Transformation Wuppertal" (WTW). Methodologically, the article builds on a review of RWL-related approaches for collaborative, intervention-oriented research. This includes transition management, transdisciplinary process models and action research. Based on this review, eight key components for RWLs are proposed. They position RWLs as a normatively framed approach that aims to contribute to local action for sustainable development and the empowerment of change agents. The approach uses transdisciplinary methods of knowledge integration and engages in cyclical real-world interventions within certain spatial and content-related boundaries. The components are transferred into a flowchart, detailing process steps, aims, responsibilities and overall principles for putting RWLs into practice. Thus, a hitherto missing tool for designing and running RWLs is provided. Then, the RWL in the district of Mirke, Wuppertal, is used as an empirical example to illustrate the application of the flowchart and related key components. Consecutive discussions centre on the different roles of researchers and practitioners in the research process, as well as the relevance of an underlying theory of change for effective interventions. Finally, critical reflection, application and amendment of the proposed flowchart are encouraged.
Keywords: Forschungsmethode; Planungsmethode; Partizipation; Nutzer; Wissenschaft; Planungspraxis; Reallabor; Nachhaltigkeit; Transformation; Qualitative Sozialforschung; Evaluation